Volume 1: Turbomachinery 1995
DOI: 10.1115/95-gt-084
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Shock/Boundary-Layer Interaction in a Highly Loaded Compressor Cascade

Abstract: Experimental investigations of the shock/boundary-layer interaction were carried out in a highly loaded compressor cascade under realistic turbomachinery conditions in order to improve the accuracy of semi-empirical flow and loss prediction methods. Different shock positions and strengths were obtained by variations of inlet flow angle and inlet Mach number. The free stream turbulence intensity, depending on the inlet Mach number, changed between 4% and 8%. The influence of the inlet Reynolds number based on b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…The compressor cascade V103-220 shown in Figure 4 is chosen as the verification model. It was designed for the hub section of a stator blade in a highly loaded axial compressor (Bell & Fottner, 1995;Hilgenfeld, Cardamone, & Fottner, 2003). This compressor cascade is constructed by conventional NACA-65 blades with a circular camber line.…”
Section: Validation Of Numerical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The compressor cascade V103-220 shown in Figure 4 is chosen as the verification model. It was designed for the hub section of a stator blade in a highly loaded axial compressor (Bell & Fottner, 1995;Hilgenfeld, Cardamone, & Fottner, 2003). This compressor cascade is constructed by conventional NACA-65 blades with a circular camber line.…”
Section: Validation Of Numerical Methodsmentioning
confidence: 99%
“…In view of these facts, the V103-220 compressor cascade is considered to be an appropriate model for investigating inverse design under high subsonic and transonic flow regimes. More detailed information about the test facility and measuring techniques of this compressor cascade can be found in Bell are Fottner (1995) and Hilgenfeld et al (2003).…”
Section: Validation Of Numerical Methodsmentioning
confidence: 99%
“…The blade aspect ratio is therefore h/lˆ1.36. The ow can be considered two-dimensional in the mid-span section for the investigated Mach and Reynolds number range, as con rmed by the oil ow visualizations performed on the blade surface [10].…”
Section: Compressor Cascadementioning
confidence: 99%
“…Some of the rst detailed experimental studies of shock/boundary layer interactions in compressor cascades include the work of Schreiber and Starken [8] and Schreiber [9] for strong shock/turbulent boundary layer interference. Bell [10] showed that the interaction of the shock with a laminar or transitional boundary layer produces signi cantly different effects on the ow behaviour in compressor cascades in comparison with shock/turbulent boundary layer interaction. Only a few experiments have been carried out for Mach and Reynolds numbers representative of real turbomachinery conditions with moderate preshock Mach numbers and laminar/transitional boundary layer interaction, such as the investigations by Fuchs et al [11] and Bell [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation